Investigation of T4 and T6 heat treatment influences on relative density and porosity of AlSi10Mg alloy components manufactured by SLM. (January 2020) - Majeed, Arfan; Zhang, Yingfeng; Lv, Jingxiang; Peng, Tao; Atta, Zahid; Ahmed, Altaf
Highlights: Influences of process parameters on densification and porosity of AlSi10Mg samples. Influences of heat treatments on the densification and porosity. The densification was enhanced with reduction in porosities by T6-heat treatment. Optimized parameters are beneficial for designers to manufacture AlSi10Mg parts. Abstract: High-quality manufacturing has particular importance in the Industry 4.0 era. Additive manufacturing (AM) is among the core technologies of industry 4.0, and selective laser melting (SLM) is among its best techniques in manufacturing of near-full dense parts. To ensure densification and porosity free products, the influence of processing parameters and heat treatment conditions should be understood. The aim of this paper is to study the effect of processing parameters and heat treatments such as T4 (solution heat treatment) and T6 (artificial aging) on the densification and porosity of AlSi10Mg parts built by SLM. The results showed that the best densification with minimum porosities was attained at the energy density of 144.89 J/mm 3 . It was confirmed from optical microscopic and SEM images that highly dense parts had lower porosity. We have also optimized the processing parameters by applying statistical analysis for the fabrication of fully dense components. Finally, it is concluded that the densification is enhanced to 99.94% by applying T4-HT at 530 °C and 99.87% in T6-HT, and porosities are also reduced by the heat treatments due to fine grain structure and strong bonding among the powder particles.